EVALUATION OF THE FUTSAL ATHLETE TRAINING PROGRAM IN THE CITY OF SAWAHLUNTO - Andri Tri Rahmanda; Anton Komaini (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
The based on observation, the futsal team of the city of Sawahlunto has not achieved maximum performance. This is allegedly because the training program given to athletes is not running optimally. This research is qualitatative research using CIPP method (Context, Input, Process, Product). This research data was obtained through observation, interviews, and documentation. The result of the study show that (1) the purpose of the Sawahlunto City futsal athletes development program is to achievement. (2) avaibility of document in written form regarding planning exercises concerning basic aspects of futsal techniques, physical, mentally and skills training program, but the calendar for training and competition programs is still unclear. The facilities and infrastructure in the futsal team of the City of Sawahlunto are now sufficient, but the practive site is still renting because the futsal team in Sawahlunto City dos’nt have is own futsal field (3) the board support the the coaching program provided by the trainer, and the change in the attitudes and insight of athletes during the coaching program, nomaly the attitude of respecting friends and appreciating opponents. Abstrak Berdasarkan pengamatan, tim futsal kota Sawahlunto belum mencapai kinerja maksimal. Ini diduga karena program pelatihan yang diberikan kepada atlet tidak berjalan optimal. Penelitian ini adalah penelitian kualitatif dengan menggunakan metode CIPP (Konteks, Input, Proses, Produk). Data penelitian ini diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa (1) tujuan program pengembangan atlet futsal Kota Sawahlunto adalah untuk berprestasi. (2) ketersediaan dokumen dalam bentuk tertulis mengenai latihan perencanaan mengenai aspek dasar teknik futsal, program pelatihan fisik, mental dan keterampilan, tetapi kalender untuk program pelatihan dan kompetisi masih belum jelas. Fasilitas dan infrastruktur di tim futsal Kota Sawahlunto sekarang sudah cukup, tetapi tempat latihan masih menyewa karena tim futsal di Kota Sawahlunto tidak memiliki lapangan futsal sendiri (3) dewan mendukung program pelatihan yang diberikan oleh pelatih, dan perubahan sikap dan wawasan atlet selama program pelatihan, menandakan sikap menghargai teman dan menghargai lawan.